Comprehensive pan-cancer analysis on CBX3 as a prognostic and immunological biomarker - Hongjuan Niu; Peiqiong Chen; Lu Fan; Boyu Sun (BMC, 2022)
Abstract Background Increased evidence supports the relationship between chromobox protein homolog 3 (CBX3) and tumorigenesis of some cancers. However, the role of CBX3 in pan-cancers remains poorly defined. In the research, we aimed to investigate the prognostic value and the immunological functions of CBX3. Results We explored the potential oncogenic roles of CBX3 in mRNA and protein levels based on the diverse databases, including the expression, the correlation with prognosis, tumor microenvironment (TME), DNA methylation, protein phosphorylation and enrichment analysis across all TCGA tumors. The results show that CBX3 is overexpressed in multiple cancers, and significant correlations exist between high expression and adverse prognosis in most tumor patients. We observed an enhanced phosphorylation level in uterine corpus endometrial carcinoma, colon cancer and lung adenocarcinoma. A distinct relationship was also found between CBX3 expression and TME, including immune infiltration of tumor-infiltrating lymphocytes and cancer-associated fibroblasts, immune score or matrix score, immune checkpoints. The correlative transcription factors and miRNAs of CBX3-binding hub genes were analyzed to investigate the molecular mechanism. Moreover, alcoholism and alteration of DNA cellular biology may be involved in the functional mechanisms of CBX3. Conclusion The first pan-cancer study offers a relatively comprehensive cognition on the oncogenic roles of CBX3 as a prognostic and immunological marker in various malignant tumors.